2015
DOI: 10.3389/fpsyg.2015.00262
|View full text |Cite
|
Sign up to set email alerts
|

The complex duration perception of emotional faces: effects of face direction

Abstract: The perceived duration of emotional face stimuli strongly depends on the expressed emotion. But, emotional faces also differ regarding a number of other features like gaze, face direction, or sex. Usually, these features have been controlled by only using pictures of female models with straight gaze and face direction. Doi and Shinohara (2009) reported that an overestimation of angry faces could only be found when the model’s gaze was oriented toward the observer. We aimed at replicating this effect for face d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
2
10
0
1
Order By: Relevance
“…One possible explanation for the discrepancy in findings is the fact we presented a three quarter view of the faces. Kliegl et al (2015) found that head direction influenced the perception of emotional expression. Participants were more likely to categorize a face as angry versus neutral, when the head was facing the participant, and likelihood reduced with degree of aversion.…”
Section: Static and Dynamic Emotion Recognition In Cu-traitsmentioning
confidence: 99%
“…One possible explanation for the discrepancy in findings is the fact we presented a three quarter view of the faces. Kliegl et al (2015) found that head direction influenced the perception of emotional expression. Participants were more likely to categorize a face as angry versus neutral, when the head was facing the participant, and likelihood reduced with degree of aversion.…”
Section: Static and Dynamic Emotion Recognition In Cu-traitsmentioning
confidence: 99%
“…The time bisection task was instead used to measure the modulation on the spatial representation of time caused by PA. The paradigm is a well-established task in which participants classify whether a series of stimuli are closer in duration to a “short” reference or to a “long” reference duration [ 55 57 ]. In order to compare the temporal and spatial changes induced by PA, we needed similar stimuli to be employed in the two tasks.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation is that the ecological significance of facial emotion among humans highly arouses the perceiver, speeding up the pulse generator, leading to an overestimation of the amount of time that has passed. Recent research has provided empirical evidence of this ecological significance (Doi and Shinohara, 2009 ; Kliegl et al, 2015 ), showing that the time-drag effect is maximal if an angry expression is presented directly to participants, whereas the effect diminishes when the gaze moves away. Such observations could be linked to the neuroanatomical pathway that enables preferential processing of affective stimuli in the amygdala (LeDoux, 2003 ).…”
Section: Introductionmentioning
confidence: 99%